Pendidikan Life Skill Santri di Pondok Pesantren Nurul Yaqin Ringan-Ringan Pakandangan - Anwar Hidayat; Akhyar Hanif; Risman Bustamam (IAIN Batusangkar, 2022)
This study investigates how students at Nurul Yaqin Islamic Boarding School in Ringan-Ringan Pakandangan are taught about life skills. The context of this study is that students acquire not just theological knowledge but also practical life skills that allow them to apply the outcomes of their own work. In order to know the inputs and outcomes of students' life skills, as well as the supporting and inhibiting factors, this study intends to determine the process of life skills education. A case study design was used in the qualitative research method. The techniques used to collect the data were observation, interviewing, and documentation. The researcher used interactive analysis to analyze the data and triangulated the data to check its trustworthiness. The findings of the study were as follows: first, the process of teaching life skills was divided into four stages: planning, paying attention, practicing, and habituation. Nurul Yaqin Islamic Boarding School in Pakandangan has the following supporting elements for life skills teaching: (1) Adequate life skills education equipment; (2) Discipline and sincerity of alumni teachers who teach life skills education; and (3) there was interest in students. While, lack of a suitable setting for practice was a barrier to life skills education at Nurul Yaqin Islamic Boarding School in Pakandangan. Third, the outcomes and outputs of life skills education at Nurul Yaqin Islamic Boarding School were as follows: (1) There were already students who were autonomous, successful in using their abilities, and able to assist their parents financially. (2) Alumni have started successful businesses in their particular fields, including furniture stores, sewing shops, and computer repair shops, among others.